PRELIMINARY STUDY OF HDBSCAN AND ISOCHRONE CURVES TO DETERMINE THE AGE OF OPEN CLUSTER IC 1590 - Adam Alifka, Fadhilla
One of many ways to study galaxies is to study the components found within them, such as open clusters which are located in the disk of the galaxy. The observed group characteristics can be used to determine other unobservable properties, such as age. By knowing the various properties of clusters, we can study galaxies more deeply. Determining the age of a star in a cluster can be done using isochrone fitting. But before that, we must be able to determine the grouping of stars that belong to a cluster. The grouping of clusters is called clustering. One of the methods used for clustering is HDBSCAN. In HDBSCAN, for min_samples and min_clusters_size we will be using 12 and 11. The results obtained from HDBSCAN are then fitted to the most suitable isochrone. Isochrone data that we will be using are obtained from http://stev.oapd.inaf.it/cgi-bin/cmd using age ranging between 5.9 - 7.9 according to Dias et al. (2002), and metallicity 0.0083 - 0.0153. Thus we will obtain log value t = 6.395, with an error of about 5% of the log value t obtained from catalogs and reference papers. Log value t obtained from the catalog Dias et al. 2002 and the Guetter and Turner paper (1997) give log value t = 6,54.